ESPOROTRICOSE EM FELINO: RELATO DE CASO - SCHOENMEIER WOECICHOSHI , JÚLIA; BECK , CRISTIANE; DA SILVA CAYE , TAYSA; PISSININ COPETTI , GABRIEL (Salão do Conhecimento, 2020)
Relato de caso acompanhado na rotina do Hospital Veterinário da UNIJUI